Religion, culture and society : a global approach - Singleton, Andrew, 1970- (Los Angeles : SAGE, 2014)
The proposal is for a modular text in the sociology of religion. The field shades into Theology/Religious Studies but the core market is sociology of religion.
Part I. Making sense of religion and religious change : theoretical and methodological approaches -- Part II. Winds of change : religion and spirituality in a globalized world.
Includes bibliographical references (226-248) and index.
Description based on MARC record for print version.
Keywords: Religion and sociology